Maximal accelerations for twelve weeks elicit improvement in a single out of a collection of cycling performance indicators in trained cyclists - Hyttel, Magnus K.; Kristiansen, Mathias; Hansen, Ernst A. (Frontiers in Sports and Active Living, 2023)
Cycling is a time-consuming sport and cyclists, therefore, focus on training effectively. The present study tested the hypothesis that twelve weeks of supplementary special training caused more favourable changes in cycling performance indicators as compared to changes measured in comparable control cyclists. Trained to well-trained cyclists (n=24) participated. A control group and a group performing special training, as a supplement to their usual cycling training, were formed. The special training consisted of series of ten repetitions of outdoor brief maximal accelerations, which were initiated from low speed and performed in a large gear ratio. The cyclists in the control group performed their usual cycling training. Performance indicators, in form of peak power output in a 7-s maximal isokinetic sprint test, maximal aerobic power output in a graded test, and submaximal power output at a predetermined blood lactate concentration of 2.5 mmol l-1 in a graded test were measured before and after the intervention. Peak power output in the sprint test was increased (about 4% from before to after the intervention) to a larger extent (p=0.045) in the cyclists who had performed the special training than in the cyclists in the control group. Changes in maximal aerobic power output and in submaximal power output at a blood lactate concentration of 2.5 mmol-1 were not significantly different between the groups (p>0.050). The results indicated that the applied supplementary special training caused moderate favourable changes of performance indicators, as compared to the changes measured in a group of comparable control cyclists.